2015
DOI: 10.1371/journal.pone.0135471
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal and Postpartum Evening Salivary Cortisol Levels in Association with Peripartum Depressive Symptoms

Abstract: BackgroundThe biology of peripartum depression remains unclear, with altered stress and the Hypothalamus-Pituitary-Adrenal axis response having been implicated in its pathophysiology.MethodsThe current study was undertaken as a part of the BASIC project (Biology, Affect, Stress, Imaging, Cognition), a population-based longitudinal study of psychological wellbeing during pregnancy and the postpartum period in Uppsala County, Sweden, in order to assess the association between evening salivary cortisol levels and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
50
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 88 publications
3
50
0
Order By: Relevance
“…Similar to oxytocin, cortisol's highly nuanced relationship with PPD may be moderated by a range of individual and contextual factors. Not surprisingly, given the diurnal variation of cortisol, the timing of cortisol measurement appears to play a role in this relationship, with some studies reporting reduced cortisol levels in mothers with PPD in the morning but not at other times of the day . It is important to observe here that this is in contrast to the link established between elevated morning cortisol and non‐postpartum MDD .…”
Section: Maternal Hormones In Postpartum Depressionmentioning
confidence: 71%
“…Similar to oxytocin, cortisol's highly nuanced relationship with PPD may be moderated by a range of individual and contextual factors. Not surprisingly, given the diurnal variation of cortisol, the timing of cortisol measurement appears to play a role in this relationship, with some studies reporting reduced cortisol levels in mothers with PPD in the morning but not at other times of the day . It is important to observe here that this is in contrast to the link established between elevated morning cortisol and non‐postpartum MDD .…”
Section: Maternal Hormones In Postpartum Depressionmentioning
confidence: 71%
“…19 In addition, another study found that higher levels of pCRH during mid-pregnancy were associated with depressive symptoms at 3-months postpartum. 20 Together, these studies support the hypothesis that changes in certain HPA markers (sCORT and pCRH) may be associated with increased depressive symptoms in the postpartum period.…”
Section: Discussionmentioning
confidence: 99%
“…Cortisol is the end product of the hypothalamic-pituitary-adrenal (HPA) axis and is required for fetal development (Nathanielsz et al, 2003). In their study, Iliadis et al (2015) determined that the cortisol levels measured in the evening in women who did not show depressive symptoms in the postpartum period were 1.19 nmol/L. Salivary cortisol levels show great differences between individuals and between different conditions or tests.…”
Section: Discussionmentioning
confidence: 99%